Hybrid Religious Engagement: Generation Z’s Negotiation of Faith Across Digital and Physical Spaces - Saputra, Dedi (Ath Thariq Jurnal Dakwah dan Komunikasi, 2025)
This article discusses the phenomenon of hybrid religious engagement among Generation Z students at the Riyadlatul Ulum Islamic Boarding School, Batanghari, East Lampung. Born and raised in the digital era, Gen Z students not only interact with traditional religious authorities in the Islamic boarding school environment, but also actively access, interpret, and distribute religious narratives from various digital platforms. This study aims to examine how students negotiate their religious beliefs, practices, and identities amidst the tension between Islamic boarding school traditions and digital religious populism. This study uses a qualitative approach with a case study method and data collection techniques in the form of in-depth interviews with six informants, male and female students. The results of the study indicate that the consumption patterns of digital content by students are selective, reflective, and adaptive. The tension between traditional authority (such as yellow books and kiai fatwas) and digital narratives (viral preaching, instant interpretation) gives rise to a complex dialectic, but at the same time encourages the construction of a new religious identity called "digital students." In this case, students are not merely in a passive position, but rather active as epistemological and cultural mediators who try to integrate traditional heritage with contemporary Islamic expressions. This article concludes that Gen Z religiosity in Islamic boarding schools has undergone a significant transformation towards a form of fluid, contextual, and multidimensional involvement, while also marking the importance of a new reading of the dynamics of young generation Islam in a digital context.